PERAN KAJIAN KITAB BIDAYATUL HIDAYAH SEBAGAI PEDOMAN IBADAH SANTRI (studi kasus di Madrasah Mu’alimin Tebuireng Jombang) - Lutfie fachrur razie (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2019)
The study of the yellow book in the boarding school cannot be doubted. The book taught in Islamic boarding schools is so diverse. One of them is the Bidayatul Hidayah book which discusses the study of the problem of ubudiyah. Bidayatul Hidayah Book is a book that is so important to be studied and used as a reference in carrying out daily worship activities. This book contains worship rules in different chapters. problems that exist in Islamic boarding schools, not all santri are able to perform worship, especially mahdah worship such as prayer in accordance with Islamic Shari'a. The focus of this research is to find out the quality of the Mu'alimin Tebuireng Jombang Madrasah worship and how the study role of the Bidayatul Hidayah book as a guide for santri worship at Mu’alimin Tebuireng Jombang Madrasah. This research method uses (1) Approaches and Types of Research (2) Research Attendance (3) Research Background (4) Research Data and Sources (5) Data Collection Techniques (6) Data Analysis Techniques. From the results of the analysis, it can be explained that the quality of santri worship in the Mu'alimin Tebuireng Jombang Madrasah is that not all santri are able to worship in accordance with Islamic law, both in terms of reading and movement.Conclusions from the results of the author's research, The role of the study of Bidayatul Hidayah as a guideline for santri is very influential on the development of the quality of santri worship, so that the quality of worship of the santri has increased.Keywords: The Book Bidayatul Hidayah, Santri Worship Guidelines